Search 75,900 tutors
Ask a question

Answers by Asok B.

1+sec^2xsin^2x= sec^2x (answer)

1+ Sec^2 X. Sin^2 X = 1 + 1/(cos^2 X). Sin^2 X = 1 + Sin^2 X/cos^2 X = 1+ tan^2 X =Sec^2 X

vu-4u+2vu-u (answer)

vu-4u+2vu-u = vu+2vu-4u-u =3vu-5u =u(3v-5)

angle of elevation (answer)

If 'h' is the height of the building, and X is the distance, then h/x =  tan 35  therefore, x/h= 1/tan35     .....(1) When he moves  100 feet toward the building the angle changes to 400 so h/x-100 = tan 40 therefore ( x-100) /h = 1/tan 40 So x/h-100/h...

angle of elevation (answer)

It will be easier to visualize once you draw a figure.  If h is the elevation  of the baloon, then,  (h-75)/(300)= Tan 200 Therefore, h-75= 300 tan 200 So,  h= 75 + 300 x tan200

(Sec theata+ Csc theata)(cos theata+ sin theata) (answer)

(Sec x + Csc x)(cos x+ sinx) ..... I used x instead of theata = [1/cos x + 1/sinx] (cosx +sinx) = [(sinx+ cosx)/cosxsinx]/ (cosx+sinx) = 1/cosxsinx =(1/cosx)x(1/sinx)= Secx Cosecx   Now you can replace theata for x.  

A certain mountain has an elevation of 19,570 feet. (answer)

In 96 years total loss is 9 acres.  Therefore yearly loss= 9/96 Acres/year =  0.09375 acres/year If  Loss of acreage is L in time "t"  years, then L= 0.09375t.  So the Equation is A= A0 - 0.09375t where A0 is the initial acreage and A is the acreage after...

integral 1/(sin(x)+cos(x)) (answer)

 Int  dx/(sinx+cosx)=  Int  (cosx-Sinx)dx/(Cos2x-sin2x)= Int  cosx dx/ (1-2Sin2x) - Int sinx dx/ (2cos2x-1) ..(.1) Let  1-2sin2x =u   and 2cos2x-1 =v so, du= -2 (2)cosx dx =-4cosx dx, thus cosx dx = -1/4 du........(2) and dv= -2 (2) sinx dx = -4sin...

find the product (answer)

(x-4)² + (x-2)² + (x-3)² = x2 -8x+16 + x2 -4x +4 + x2-6x +9 = 3x2-18x +29

Solve the equation (answer)

(2r + 1 )( r -2 ) = - (3r -6 ) 2r2+ r-4r-2 = -3r+6 2r2-3r-2=-3r+6 2r2=8 r2=4 Thus r= +2 or -2

f(x)= [3x]+3 (answer)

f(x)=3x+3 is not an equation. It's a line with the slope 3 and an Y-intercept of 3.

need help with math (answer)

Hi Jaelyn, Your equation seems to be 13= g/3 +4 and not 13= g/ (3+4) as understood by Marissa. If we rearrange it, g/3= 13-4=9   and hence g=9x3 =27